Cyclic fatigue effect in particulate ceramic composites. Issue 14 (November 2016) - Lugovy, M.; Slyunyayev, V.; Orlovskaya, N.; Reece, M.; Graule, T.; Kuebler, J.
Abstract: A new model is presented that provides an improved understanding of the time dependent fatigue behavior of two phase brittle particulate ceramic composites under static and cyclic loading conditions. The proposed model takes into consideration cyclic fatigue effects, which are responsible for the accelerated fatigue crack propagation in the cyclic loading as compared to the static loading. It also takes into account the effect of both thermal residual stresses and bridging stresses acting in the composite during time dependent crack propagation. Experimental results for the fatigue behavior of ZrB2 –45 vol%SiC ceramic composite were used as a case study to valid the proposed model. The model gives insight both into the time dependent mechanical behavior of ceramic composites and, at the same time, allows determination of important structural parameter, such as, size of the bridging zone in the material under cycling loading.